2022
DOI: 10.1039/d1tb02802b
|View full text |Cite
|
Sign up to set email alerts
|

Icariin-loaded sulfonated polyetheretherketone with osteogenesis promotion and osteoclastogenesis inhibition properties via immunomodulation for advanced osseointegration

Abstract: Preventing prosthesis loosening due to insufficient osseointegration is critical for patients with osteoporosis. Endowing implants with immunomodulatory function can effectively enhance osseointegration. In this work, we loaded icariin (ICA) onto...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The mass spectrometry conditions were as follows: Electrospray ionization (ESI) was used to collect data in positive and negative ion modes. The desolvation gas flow was 800 L h À1 , the desolvation temperature was 450 1C, the cone gas flow was 50 L h À1 , the source temperature was 120 1C, the positive ion capillary voltage was 3 kV, the negative ion capillary voltage was 3 kV, the sampling cone voltage was 40 V, the scanning mode was full scan, and the scanning range was m/z 150-2000 for MS 1 and m/z 100-1800 for MS 2 . The software Peakview was used to analyze mass spectrometry data.…”
Section: Lc-ms Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometry conditions were as follows: Electrospray ionization (ESI) was used to collect data in positive and negative ion modes. The desolvation gas flow was 800 L h À1 , the desolvation temperature was 450 1C, the cone gas flow was 50 L h À1 , the source temperature was 120 1C, the positive ion capillary voltage was 3 kV, the negative ion capillary voltage was 3 kV, the sampling cone voltage was 40 V, the scanning mode was full scan, and the scanning range was m/z 150-2000 for MS 1 and m/z 100-1800 for MS 2 . The software Peakview was used to analyze mass spectrometry data.…”
Section: Lc-ms Analysis Methodsmentioning
confidence: 99%
“…was first recorded in the text Shen Nong's Herbal Classic, which has been used for more than 2000 years. [1][2][3] Currently, there are about 40 species of Epimedium in the world, and 8 species of Epimedium medicinal herbs circulating in the market, including Epimedium koreanum Nakai, Epimedium brevicornum Maxim., Epimedium pubescens Maxim., Epimedium sagittatum (Sieb. et Zucc.)…”
Section: Introductionmentioning
confidence: 99%
“…Experimental findings demonstrated that the developed scaffolds effectively loaded and released ICA over an extended period. Furthermore, various biomaterials have been investigated to enhance the loading efficiency and bioavailability of ICA, including β-TCP [ 145 ], PLGA [ 146 ], calcium phosphate cement [ 147 ], 3D porous polydopamine/sulfonated PEEK [ 148 ], TiO 2 nanotube/PLGA [ 149 ], titanium [ 150 , 151 ], PCL/gelatin fibers [ 152 ], SF/PLCL nanofibrous scaffold [ 153 ], PLLA/PDA/chitosan [ 154 ], biphasic calcium phosphate (BCP) [ 155 ], polyvinyl alcohol (PVA)/β-TCP [ 156 ], hydroxyapatite/chitosan [ 157 ], hydroxyapatite/alginate porous composite [ 139 ], nanohydroxyapatite/polylactic acid (nHAP/PLA) [ 158 ], and PLGA/β-TCP [ 140 ].…”
Section: Icariin-loaded Nanoplatformsmentioning
confidence: 99%
“…Ouyang et al have demonstrated that sulfonated PEEK exhibited significant antibacterial properties against Staphylococcus aureus and Escherichia coli. The high specific surface area and roughness of the 3D porous network make it an ideal carrier for functional biomolecules, thus endowing it with additional biological functions. Moreover, several studies have indicated that the 3D interconnected porous network can be used as a drug delivery platform, offering the possibility of achieving stable and slow drug release. …”
Section: Introductionmentioning
confidence: 99%